Evaluation of the oral dental health status of the Romani community in Turkey - Elif Koçak; Bahar Alkaya (Cukurova Medical Journal, 2021)
Purpose: This study was conducted to determine the oral and dental health levels of individuals of a specific ethnic origin (Romani) living in Turkey and investigate its effects on quality of life. Materials and Methods: The study was carried out in Adana (Yüreğir) between October 2018 and July 2019. Data were collected from 183 Romani individuals using face-to-face interview technique, an introductory information form, a form evaluating oral hygiene habits, and the Oral Health Impact Profile (OHIP) -14 scale. The number of dental caries, the number of missing teeth, and periodontal health levels, halitosis, and toothbrushing habits were evaluated by performing intraoral examinations of the participants. Results: The OHIP-14 score of the individuals participating in the study showed a statistically significant change according to the number of missing teeth, the number of dental caries teeth, and brushing habits. Accordingly, the OHIP-14 score was observed higher in individuals with extracted teeth and decay in teeth. No statistically significant correlation was found between periodontal parameters and OHIP-14 scores. Conclusion: Within the limitation of the study; It is thought that oral-dental health knowledge levels and oral hygiene habits should be increased in Romani individuals.